2008
DOI: 10.1007/s10995-008-0377-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Public Health Data Linkages

Abstract: The computer-matched records evaluated were sufficiently accurate. This provides a unique source to public health practitioners and researchers to perform epidemiological studies that could not be possible with single sources data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Moreover, it is not always possible to trace all individuals; consequently the active follow up is also prone to errors 19,24,25 . Another strategy is to manually inspect a random sample of links designated as matches and non-matches by two independent reviewers with the human judgment being considered the gold standard 26 . This procedure might be timeconsuming and because of its subjective nature, it is also subject to error.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is not always possible to trace all individuals; consequently the active follow up is also prone to errors 19,24,25 . Another strategy is to manually inspect a random sample of links designated as matches and non-matches by two independent reviewers with the human judgment being considered the gold standard 26 . This procedure might be timeconsuming and because of its subjective nature, it is also subject to error.…”
Section: Discussionmentioning
confidence: 99%
“…Qayad et al compared the PRAMS data set to birth certificate data and reported 90% agreement between the PRAMS survey and the computer-matched files. 6 The information in the PRAMS database is gathered from surveys that are sent to women who deliver a live-born infant within New Jersey. The New Jersey PRAMS questionnaire is built around a mandatory core developed by CDC.…”
Section: Methodsmentioning
confidence: 99%
“…184,198,200,201 In probabilistic linkage, a pair of records from two datasets are classified as belonging to the same individual, or not, based on the statistical probability that common identifiers in the datasets belong to the same entity, using weights or scores to gauge the agreement and disagreement between the records. 184,[193][194][195]202,203 The statistical probability, and not the evidence of an exact match, as needed in deterministic approaches, is then used to decide whether a pair of records refers to the same entity. Probabilistic linkage is therefore more suitable in exercises where unique identifiers are not available, or where there is evidence of variation in reporting, coding or transcription of identifiers.…”
Section: Record Linkage Approachesmentioning
confidence: 99%
“…203 In particular, advances in the affordability and capacity of computing equipment were an enabling factor. 175 Linkage activities moreover increased as a result of researchers and research institutions departing from traditional methods that are prohibitively resource-consuming-in terms of financial costs, and human-resource and infrastructural investments-and likely subject to complicating factors referred to before.…”
Section: Increased Linkage: Reasons and Enabling Factorsmentioning
confidence: 99%
See 1 more Smart Citation